Water productivity simulation for irrigated farmlands in the Brantas River Basin - Raymond Valiant; Waego Hadi Nugroho; Mohammad Bisri; Wani Hadi Utomo (Journal of Degraded and Mining Lands Management, 2021)
Simulation of land and water management for the irrigated farmlands has become an interest to answer how agricultural productivity is related to the water use in a river basin. This research was undertaken in the Brantas River Basin in Indonesia, involving a modelling process with the virtual water concept as a tool to analyze water productivity. The research simulated the agricultural water demand and provided the results of the virtual water content of paddy and maize, based on the available farming land, water availability, cropping pattern and climatological conditions of the respective hydrological years of 1997 and 2011 as a benchmark. After which projections were made based on the low rainfall scenario for the years 2021 to 2025. The research concluded that the presence of excess irrigation in the tropical climates hinders the increase in agricultural productivity, and therefore, the irrigation in the Brantas River Basin needs to be improved by, among others, selecting plants with higher water productivity, developing water-sensitive cropping patterns, and water conveyance savings.